Changes in household composition in South Africa (2002 –2018) from a gender perspective - Goagoses, Linekela Frieda Karolina (My University, 2021)
This paper assesses patterns and trends of gender differences in household composition and access to resources in South Africa between 2002 and 2018. Instead of using headship, households are identified as female-dominated (all adults are female), male-dominated (all adults are male) or mixed (both female and male adults are present). Using General Household Survey (GHS) data, this study finds that household formation is outpacing population growth and is fastest among male-dominated households, with female-dominated households having the second-fastest rate of household formation. Amongst households that contain adults, mixed households have the lowest rate of household formation, partly explained by declining rates of marriage. The increase in the number of households is driven by the rise of single-person households, and this combined with falling fertility rates explains the observed decline in average household size. Female-dominated households are more economically precarious than both male-dominated and mixed households because they are less likely to report earnings as the main source of income; and compared to male-dominated households, they are larger and more likely to include children. This paper contributes to the literature by providing an assessment of recent patterns and trends in household composition in South Africa. In addition, it demonstrates that an alternative to household identification by headship, gender composition of adults, is useful for tracing gender differences in access to resources
A research report submitted in partial fulfilment of the degree of Master of Commerce (Applied Development Economics) in the School of Economics and Finance, University of the Witwatersrand